Semiotics of law for the study of judicial precedents - Col, Juliana Sípoli; de Souza, Paulo Roberto (Laboratório Editorial FCL-UNESP, 2010)
The study of judicial precedents, primarily applied in countries of the common law system, has been enhanced in Brazil; not only with the application of persuasive judicial precedents, which may be models to judges of future cases based on the same facts of demands previously decided, as the binding precedents, based on the theory of stare decisis, as the example, in Brazilian law, of the binding summary, that is a blending of rule of law and judicial decision, what allows us to call it judicial rule of law. The application of Semiotics for judicial precedents study demonstrates that this science is an adequate and effective theoretical instrument, especially in its pragmatic perspective, by the application of abduction, method which matches with the outlook in future of judicial precedents, in order to speak of the emergence in national scenario, of the Semiotics of Law, whose object of study is Law and, particularly, judicial precedents.